Analysis of Development and Spatial Pattern of Minimarket Distribution in Kaliurang Road Corridor - Alpeus Manihuruk (Pascasarjana, Universitas Negeri Padang, 2021)
Minimarket is the most expansive retail because the growth in number is much larger than other retail such as supermarkets and hypermarkets. In addition, the existence of minimarkets can not only be found in big cities but can also be found on the suburban and even rural areas. The spatial distribution of minimarkets in regional space is not random but forms a certain pattern that can be analyzed and mapped.Technological developments in the geospatial field, especially Geographic Information System (GIS) technology provide convenience in analyzing data on objects on the earth's surface, especially the development and spatial pattern of minimarket distribution in the Kaliurang road corridor. The analysis used in this study is trend analysis, which is to explain the direction and trend of minimarket development; and nearest neighbor analysis, which is to find out the spatial pattern of minimarket distribution that is formed in the Kaliurang road corridor.The results show that the direction of minimarket development is in line with the physical development of the city. In other words, the more developed an area, the higher the development of existing minimarkets, namely towards the southern part (urban area appearance) of the Kaliurang road corridor. Meanwhile, the physical development of the area also affects the distribution pattern formed. A clustered pattern is formed in urban areas apperance (T=0.83), a random pattern in suburban areas (T=1.22), and a spreading pattern in rural areas (T =2.78).